The Boswell Papers (1927–2021) and the Mediated Meaning of Place. Issue 2 (August 2022) - Glover, Brian
Abstract : In 1927, the American collector Lt-Col. Ralph Heyward Isham arrived in New York with what he then thought was the entirety of the James Boswell Papers, which had been presumed lost by scholars since Boswell's death in 1795. Soon, Isham began the process of publishing them in a private-press edition limited to 570 sets, as Private Papers of James Boswell from Malahide Castle in the Collection of Lt-Colonel Ralph Heyward Isham . This essay explain the complicated beliefs about place, communication, and the meaning of paper that inhere in that seemingly simple title, arguing that the pursuit of manuscripts in a print culture represented an attempt to bring the unmappable world into the defined limits of the collector's home – an effort not at all unlike the big-game hunting for which Isham was also well known. This effort, the essay argues, has become impossible to conceptualise in a world of digital collecting.